THE SYMBOLIC MEANING RITUAL WILUJENGAN OF AGRICULTURAL SOCIETIES IN THE SLOPES OF MOUNT WILIS - Wahyuningtyas, Neni; Lailia, Ifa Matul (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
For Javanese Muslim society, rituality as a form of devotion and sincerity of worship to God, partly manifested in the form of ritual symbols that contain deep meaning. Ritual symbols are expressions or embodiments of appreciation and understanding of "inaccessible reality" to become "very close". This research was conducted at Slopes of Wilis Mountain Tulungagung Regency by using qualitative approach with descriptive research type. The results showed by the use of ritual symbols wilujengan by the slopes of Mount Wilis has the meaning of God is always present and always involved, "united" in him. The symbol of the ritual understood as the manifestation of his intent as a human being is tajalli, or as an integral part of God. It is known that in the Javanese Islamic tradition, whenever there is a change in human life cycle, on average they perform ritual wilujengan, using various food objects as a symbol of appreciation of the relationship with God.